Silver Nanoparticle-Induced Apoptosis in ARPE-19 Cells Is Inhibited by Toxoplasma gondii Pre-Infection Through Suppression of NOX4-Dependent ROS Generation - Quan JH (Dove Medical Press, 2020)
Juan-Hua Quan,1,* Fei Fei Gao,2,* Hassan Ahmed Hassan Ahmed Ismail,3,* Jae-Min Yuk,2 Guang-Ho Cha,2 Jia-Qi Chu,4 Young-Ha Lee2 1Department of Gastroenterology, The Affiliated Hospital of Guangdong Medical University, Zhanjiang 524-001, People’s Republic of China; 2Department of Infection Biology and Department of Medical Science, Chungnam National University College of Medicine, Daejeon 301-131, Korea; 3Communicable and Non-Communicable Diseases Control Directorate, Federal Ministry of Health, Khartoum, Sudan; 4Stem Cell Research and Cellular Therapy Center, Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong Province 524-001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Young-Ha LeeDepartment of Infection Biology and Department of Medical Science, Chungnam National University College of Medicine 6 Munhwa-Dong, Jung-Gu, Daejeon 35015, KoreaTel +82-42-580-8273Fax +82-42-583-8216Email yhalee@cnu.ac.krPurpose: External and internal stimuli easily affect the retina. Studies have shown that cells infected with Toxoplasma gondii are resistant to multiple inducers of apoptosis. Nanoparticles (NPs) have been widely used in biomedical fields; however, little is known about cytotoxicity caused by NPs in the retina and the modulators that inhibit nanotoxicity.Materials and Methods: ARPE-19 cells from human retinal pigment epithelium were treated with silver nanoparticles (AgNPs) alone or in combination with T. gondii. Then, the cellular toxicity, apoptosis, cell cycle analysis, autophagy, ROS generation, NOX4 expression, and MAPK/mTOR signaling pathways were investigated. To confirm the AgNP-induced cytotoxicity in ARPE-19 cells and its modulatory effects caused by T. gondii infection, the major experiments carried out in ARPE-19 cells were performed again using human foreskin fibroblast (HFF) cells and bone marrow-derived macrophages (BMDMs) from NOX4−/− mice.Results: AgNPs dose-dependently induced cytotoxicity and cell death in ARPE-19 cells. Apoptosis, sub-G1 phase cell accumulation, autophagy, JNK phosphorylation, and mitochondrial apoptotic features, such as caspase-3 and PARP cleavages, mitochondrial membrane potential depolarization, and cytochrome c release into the cytosol were observed in AgNP-treated cells. AgNP treatment also increased the Bax, Bik, and Bim protein levels as well as NOX4-dependent ROS generation. However, T. gondii-infected ARPE-19 cells inhibited AgNP-induced apoptosis, JNK phosphorylation, sub-G1 phase cell accumulation, autophagy, NOX4-mediated ROS production, and mitochondrial apoptosis. Furthermore, mitochondrial apoptosis was found in AgNP-treated HFF cells and BMDMs, and AgNP-induced mitochondrial apoptosis inhibition via NOX4-dependent ROS suppression in T. gondii pre-infected HFF cells and BMDMs was also confirmed.Conclusion: AgNPs induced mitochondrial apoptosis in human RPE cells combined with cell cycle dysregulation and autophagy; however, these effects were significantly inhibited by T. gondii pre-infection by suppression of NOX4-mediated ROS production, suggesting that T. gondii is a strong inhibitory modulator of nanotoxicity in in vitro models.Keywords: silver nanoparticles, Toxoplasma gondii, mitochondrial apoptosis, human retinal pigment epithelium, reactive oxygen species, NADPH oxidase 4